Biblical interpretation and African traditional religion : cross-cultural and community readings in Owamboland, Namibia - John, Helen C., (Biblical Interpretation Series, 2019)
In Biblical Interpretation and African Traditional Religion , Helen C. John juxtaposes grassroots biblical interpretations from Owamboland, Namibia, with professional interpretations of selected New Testament texts, effectively demonstrating the capacity of grassroots interpretations to destabilise, challenge and nuance dominant professional interpretations. John uses a cross-cultural and dialogical approach - 'Cross-Cultural Biblical Interpretation Groups' - to explore the relationship between African Traditional Religion (ATR), Christianity and biblical interpretation in Owamboland, Namibia. She contextualises the grassroots Owambo interpretations using fieldwork experiences and ethnographic literature, thus heightening the cross-cultural encounter. In particular, John reflects on Western epistemologies and the Eurocentric interpretative trends that are brought into relief by the African interpretations gathered in Owamboland.